Examining The Chemical And Biological Properties of Different Heterocyclic Rings - Kareem , Aseel (Physical Sciences, Life Science and Engineering, 2025)
Melting point, FTIR, chromatography analysis, and physical properties were used to determine the structures of new heterocyclic compounds that contained 4-aminoantipyrine, which was thought to be a crucial step for the synthesis of some new derivativesGram-positive and gram-negative bacteria (Staphylococcus aureus and Streptococcus mutans) and Shigella flexeneri and Pseudomonas aeruginosa) are evaluated for their antibacterial activity using these substances. Academics and medical applications have shown a great deal of interest in the antipyrine derivatives, which are a popular structural motif among heterocyclic compounds with three nitrogen heteroatoms. Although they are not found in nature, they are used extensively in drug development, organic synthesis, chemical biology, polymer chemistry, and supramolecular chemistry. As a result, developing a straightforward and easy method for the production of antipyrine derivatives is crucial. In contrast to conventional antibiotics, The findings demonstrated the strong antibacterial qualities of each of these substances. Additionally, we discovered that they can induce pro-inflammatory cytokines like IFN-γ, which are released by CD4+ T helper 1 (Th1) cells, to have an immunological effect in vivo in an animal model.. Therefore, this study aims to synthesize some novel derivatives and evaluate their antibacterial activity by examining their capacity to induce the cellular immune response and the histopathological changes in the experimental rabbits' splenic sections.